Mid-infrared, ultra-broadband, low-loss, compact arbitrary power splitter based on adiabatic mode evolution - Sia, Brian Jia Xu (2020)
We designed and demonstrated TE-mode arbitrary power splitters based on adiabatic mode evolution. The power splitters are designed with a footprint of smaller than 12 × 2.9 μm 2 , fabricated on a 400-nm silicon-on-insulator platform, requiring only a single etch step. The optimization process and the conditions for arbitrary-power splitting are performed using three-dimensional-FDTD simulations. We prove this concept through the fabrication of asymmetrical adiabatic evolution-based power splitters with splitting ratios of 50:50, 60:40, and 70:30. The fabricated devices are shown to agree closely with simulation results. Broadband operation with low insertion loss of 0.11-0.6 dB is demonstrated across the 3.66-3.89 μm wavelength range (230 nm). This component has applications in a multitude of areas such as spectroscopic optical sensing and optical phased arrays photonic integrated circuits etc.